Over- and under-supply of inpatient rehabilitation after stroke without a post-acute rehabilitation system: a nationwide retrospective cohort study - Bae, Suk Won; Kwon, Junhyun; Shin, Hyung-Ik (Frontiers in Neurology, 2023)
Introduction: This study aimed to investigate the utilization of post-ischemic stroke rehabilitation prior to the introduction of the post-acute rehabilitation system in South Korea in 2017. Methods: Medical resources utilized for patients with cerebral infarction hospitalized at Regional Cardio-Cerebrovascular Centers (RCCVCs) of 11 tertiary hospitals were tracked until 2019. Stroke severity was classified according to the National Institutes of Health Stroke Scale (NIHSS), and multivariate regression analysis was performed to analyze factors influencing the length of hospital stay (LOS). Results: The study included 3,520 patients. Among 939 patients with stroke with moderate or greater severity, 209 (22.3%) returned home after RCCVC discharge without inpatient rehabilitation. Furthermore, 1,455 (56.4%) out of 2,581 patients with minor stroke with NIHSS scores ≤4 were readmitted to another hospital for rehabilitation. The median LOS of patients who received inpatient rehabilitation after RCCVC discharge was 47 days. During the inpatient rehabilitation period, the patients were admitted to 2.7 hospitals on average. The LOS was longer in the lowest-income group, high-severity group, and women. Conclusion: Before the introduction of the post-acute rehabilitation system, treatment after stroke was both over- and undersupplied, thus delaying home discharge. These results support the development of a post-acute rehabilitation system that defines the patients, duration, and intensity of rehabilitation.